Agile Manufacturing Strategy and Business Ethics - Poesche, J. (Journal of business ethics, 2002)
Evolving manufacturing management strategies pose changing business ethical challenges to the companies and society. The evolution is not one that continuously improves the business ethical performance, some aspects improve it and some other are detrimental. This paper explores the business ethical implications of the evolution of manufacturing management starting at the pre-industrial workshops until the introduction of agile manufacturing based on business ethical criteria drawn from business ethics (applied moral theory) and environmental law.